Labour and Employment Policy: Opportunities and Challenges for Undergraduate Students - Mariam Davitadze (European Scientific Journal, ESJ, 2023)
The presented article discusses the mechanisms of employment and promotion of undergraduate students, which, on the one hand, will improve the socio-economic status of students, and on the other hand, will help them combine work and study. Based on the review of the international literature, the circumstances and features promoting the employment of students were studied, the challenges faced by undergraduate students in Georgia during employment were analyzed and identified. As a result of the obtained data, such hindering circumstances of employment were determined, such as unsuitable work schedule, lack of student work in the labour market, low interest of employers in employing students, wages and working hours. Based on the sources, approaches, practices and mechanisms in the world focused on the promotion of student employment, which in itself improves the socio-economic status of students and increases their motivation to study, have been identified. The article presents the advantages and disadvantages of mechanisms promoting the employment of undergraduate students and generalizes them in relation to the existing international practice. The results of the research will be of interest to state representatives and employers who employ students and face certain challenges, representatives of the education field, specialists in the field and individual experts, however, the issue of development of programs supporting the employment of students by the state, their sphere of influence and the initiatives of employers to employ students is a separate subject of research.